1987
DOI: 10.1016/0014-5793(87)81552-1
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin inhibits the angiotensin II and serotonin‐induced rise of free cytoplasmic calcium in cultured smooth muscle cells from rat aorta

Abstract: Angiotensin II, serotonin and K+-depolarization cause an increase in free cytoplasmic CaZ+ in cultured smooth muscle cells. The involvement of a guanine nucleotide-binding protein has been investigated by using pertussis toxin. When smooth muscle cells were pretreated with pertussis toxin angiotensin II and serotonin-induced rise of cytosolic Ca2+ was found to be significantly reduced whereas the Ca2+ influx mediated by K+-depolarization remained unchanged. These results suggest the participation of a guanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The complete blockade of the AII‐induced [Ca 2+ ] i rise by PTX indicates that AII raises [Ca 2+ ] i in human VSMCs via a PTX‐sensitive heterotrimeric G protein. Previous studies have concluded that G proteins are involved in [Ca 2+ ] i elevation in response to this agent in smooth muscle, but have yielded no consensus regarding PTX sensitivity (Bruns & Marme, 1987; Dostal et al , 1990; Ohya & Sperelakis, 1991). The failure of lovastatin to affect responses to AII and LDL is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The complete blockade of the AII‐induced [Ca 2+ ] i rise by PTX indicates that AII raises [Ca 2+ ] i in human VSMCs via a PTX‐sensitive heterotrimeric G protein. Previous studies have concluded that G proteins are involved in [Ca 2+ ] i elevation in response to this agent in smooth muscle, but have yielded no consensus regarding PTX sensitivity (Bruns & Marme, 1987; Dostal et al , 1990; Ohya & Sperelakis, 1991). The failure of lovastatin to affect responses to AII and LDL is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a GTP-sensitive pool in VSMC is shown by the ability of GTP[S] and NaF to stimulate inositol phosphate accumulation in a dose-dependent manner. Previous reports had suggested that hormonal signalling in VSMC was mediated by a G-protein based on observations that GTP analogues altered the affinity of the receptor for angiotensin II [43], and that pertussis toxin inhibited Ca2" mobilization in angiotensin II [17] or noradrenaline [18]-stimulated cells. In contrast with the latter reports, no sensitivity of angiotensin II-induced IP3 formation to pertussis toxin was observed here, although the concentration of pertussis toxin used in our study was sufficient to modify all of the available substrate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular action of AII in vascular tissue is initiated by hormone binding to cell surface receptors. This hormone-receptor complex, possibly in association with a specific guanine nucleotide-binding protein (1,2), activates a phospholipase in the plasma membrane (3). The subsequent hydrolysis of phosphatidyl inositol bisphosphate and phosphatidyl inositol results in the activation of inositol trisphosphate and diacylglycerol intracellular signals (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%